A new general methodology for incorporating physico-chemical transformations into multi-phase wastewater treatment process models. (1st May 2015) - Lizarralde, I.; Fernández-Arévalo, T.; Brouckaert, C.; Vanrolleghem, P.; Ikumi, D.S.; Ekama, G.A.; Ayesa, E.; Grau, P.
Abstract: This paper introduces a new general methodology for incorporating physico-chemical and chemical transformations into multi-phase wastewater treatment process models in a systematic and rigorous way under a Plant-Wide modelling (PWM) framework. The methodology presented in this paper requires the selection of the relevant biochemical, chemical and physico-chemical transformations taking place and the definition of the mass transport for the co-existing phases. As an example a mathematical model has been constructed to describe a system for biological COD, nitrogen and phosphorus removal, liquid–gas transfer, precipitation processes, and chemical reactions. The capability of the model has been tested by comparing simulated and experimental results for a nutrient removal system with sludge digestion. Finally, a scenario analysis has been undertaken to show the potential of the obtained mathematical model to study phosphorus recovery. Graphical abstract: Highlights: New methodology for biochemical, chemical and physicochemical transformation models. Methodology implemented in a plant-wide modelling methodology. Multi-matrix structure for mass transport between co-existing phases. Numerical resolution for stiff systems.